Kurumsal Yönetimin Finansal Raporlama Kalitesindeki Rolü: Borsa İstanbul Üzerine Karşılaştırmalı Bir Uygulama (The Role Of Corporate Governance On The Quality Of Financial Reporting: A Comparative Study On Borsa Istanbul) - Mahmut KARĞIN; Rabia AKTAŞ; Nuray DEMİREL ARICI (Yönetim ve Ekonomi, 2015)
Corporate governance is sum of the principles to manage businesses by an understanding that assure all of the stakeholders’ rights. The theoretical expectation is that financial reporting quality of businesses that follow the corporate governance principles increases. The purpose of this study is to investigate the impact of corporate governance on the financial reporting quality. Therefore the quality of financial reports of listed and non-listed firms in Borsa Istanbul Corporate Governance Index (XKURY) is compared with each other in terms of earnings persistence. As a result of the study, it’s seen that earnings of firms traded in XKURY are more persistent than others. It is concluded that their financial reports are more qualified.